Utility of the anterior reach Y-BALANCE test as an injury risk screening tool in elite male youth soccer players - Read, P. J.; Oliver, J. L.; Myer, G. D.; Farooq, A.; de Ste Croix, M.; Lloyd, R. S. (Physical Therapy in Sport, 2020)
Objectives: Examine growth and maturation trends in dynamic balance using the anterior reach Y-Balance test, and its utility as an injury risk screening tool. Design: Cross sectional and prospective cohort. Setting: Elite male youth soccer players. Participants: 346 players grouped as pre, circa or post peak height velocity (PHV). Main outcome measures: Pre-season anterior reach absolute and relative Y-Balance test scores and seasonal prospective lower extremity injury monitoring. Results: Absolute reach distances were greatest post-PHV (p < 0.05). Relative to leg length, pre-PHV achieved the highest scores and increased between-limb differences. Significant associations between injury and anterior reach scores were present in pre (OR: 0.94, CI: 0.91-0.98, p < 0.05) and circa-PHV (OR: 1.05, 95% CI: 1.05-1.10, p < 0.05). Increased age (OR: 1.49, 95% CI: 1.04-2.13, p < 0.05) and height (OR: 1.06, 95% CI: 0.99-1.13, p = 0.82) were risk factors post-PHV. No differences in injury occurrence were shown between players with absolute reach difference >4cm in any group. Conclusions: Anterior reach scores increased injury risk, but associations were small and inconsistent. The Y-Balance should be used with caution as a screening tool in this cohort.